Pigmentos produzidos pelo fungo basidiomiceto Pisolithus tinctorius: desreplicação, isolamento e estudo do potencial biotecnológico - Camara, Ana Gabrielle do Nascimento (2023)
Basidiomycete Pisolithus tinctorius (order Boletales) is a mycorrhizal fungus, which grows in symbiosis with Eucalyptus and Pinus trees. Pulvinic acid derivatives are major secondary metabolities produced by this fungus, responsable for its yellow, orange and brown colors. Norbadione A, badione A, bisnorbadioquinone A and pisoquinone are exemples of pigments molecules produced by P. tinctorius. In this context, this work describes the chemical profile of pulvinic acid derivatives pigments in Pisolithus tinctorius collected in Campus do Pici, at Ceara Federal University, as well as the investigation of the biotechnological potential of fractions H2O-MeOH and MeOH. The UV-vis and infrared absorption analysis showed characteristics sinals of the basic skeleton of pulvinic acid derivatives. Furthermore, the termogravimetric and fluorescence analysis were used for characterization of fractions, which presented termal stability and fluorescence properties. Dereplication analysis of fractions was developed using high performance liquid Chromatography coupled with mass Spectrometry (HPLC-MS) and molecular networking, at GNPS online platform. That was possible to propose the presence of 7 pulvinic acid derivatives already reported in the literature, among which 4 were identified for the first time in P. tinctorius, besides other molecules belonging to different class of compounds. This study also allowed the proposition of 7 novel compounds. Norbadione A, known as the major pigment of P. tinctorius, was isolate from fraction H2O-MeOH and identified by FTIR, UV-Vis, MS and NMR 1H and 13C. Fractions H2O-MeOH and MeOH showed antioxidante capacity, with EC50 22 e 105 µg mL-1, respectively. The solar protection factor of fractions was also investigated, with 23,19 for fraction H2O-MeOH and 20,34 for MeOH. Besides that, fraction H2O-MeOH had no citotoxicity against normal cells. This results indicate the great biotechnological potential of fractions, enabling its aplication in human consuption products, such as cosmetics.